Giant Cell Tumor of the Capitate Treated with Excision and Midcarpal Fusion - Oufkir, Ayat Allah; Lazerges, Cyril; Coulet, Bertrand; Chammas, Michel (Journal of Wrist Surgery, 2017)
Background Giant cell tumor (GCT) of bone is rare in the carpus, and only 11 cases have been reported in the capitate bone. The problem with this location is the high recurrence rate due to easy extension to the adjacent joint spaces and bones. We describe a case of GCT on the capitate bone and the treatment in comparison with the previously reported cases.Case Description The case report concerns a 48-year-old woman with a GCT of the capitate diagnosed on curettage. The treatment consisted of large resection with the lunatum and third metacarpal arthrodesis, with a successful union at 2 years follow-up, no recurrence, and an improved function of the wrist.Literature Review When treated by curettage (alone or with adjuvant procedures), the GCT of the capitate recurred in four out of five cases. All tumors treated with large resection did not recur.Clinical Relevance Recommended treatment of GCT of the capitate is resection with carpometacarpal arthrodesis.
Keywords: giant cell tumor; carpal bones; metacarpal arthrodesis